2015
DOI: 10.1111/nyas.12879
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: challenges in analyzing its biological effects

Abstract: Testing the biological activities of a dietary compound like resveratrol presents various challenges, which are highlighted in this commentary, with some suggested direction for future research, focusing on five challenges: (1) many different cellular effects are observed for resveratrol, but it is not known whether they arise from one point of action (or a few) or whether resveratrol is non-specific in its action; (2) the health-promotion effect of dietary resveratrol is likely a combinatory effect of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…7B). Although both ATR and ATM phosphorylate Ser 15 of p53 (60), we found no evidence that resveratrol activated an ATM-Chk2-p53-p21 pathway, a pathway that is generally activated in response to double-stranded DNA breaks. Thus, our data suggest that resveratrol triggers a replication stress-like response rather than classical DNA damage.…”
Section: S C I E N C E S I G N a L I N G | R E S E A R C H A R T I C L Ementioning
confidence: 65%
“…7B). Although both ATR and ATM phosphorylate Ser 15 of p53 (60), we found no evidence that resveratrol activated an ATM-Chk2-p53-p21 pathway, a pathway that is generally activated in response to double-stranded DNA breaks. Thus, our data suggest that resveratrol triggers a replication stress-like response rather than classical DNA damage.…”
Section: S C I E N C E S I G N a L I N G | R E S E A R C H A R T I C L Ementioning
confidence: 65%
“…Numerous preclinical studies have shown that resveratrol inhibits the growth of various cancer cell types in vitro and has convincing cancer preventive effects in various animal models . However, these effects have not yet been confirmed in humans, owing in part to the practical limitations associated with the study of human carcinogenesis in vivo …”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a naturally occurring phytochemical that is produced by plants. Resveratrol has been demonstrated to have diverse biological properties, including anti-inflammatory, antioxidant, antiviral, neuroprotective, antifungal and anticancer properties (32,33). Resveratrol has been reported to inhibit cancer cell growth via the AKT signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%